2021
DOI: 10.1016/j.xpro.2021.100809
|View full text |Cite
|
Sign up to set email alerts
|

A flow-cytometry-based assessment of global protein synthesis in human senescent cells

Abstract: Summary Senescent cells constantly experience stressful conditions and restrain their protein translation to cope with it. Here, we present a detailed protocol to measure the rate of global protein synthesis using L-azidohomoalanine (L-AHA)-based click chemistry in human senescent fibroblasts. We optimized several aspects of the procedure, including senescence induction, a flow cytometry analysis of senescent cells, and the duration of L-AHA incorporation. This protocol uses senescent human fibrobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Thus, we decided to examine whether this is also the case for woad extracts. We employed two gold-standard models of senescent cell lines: senescent human lung and foreskin fibroblasts (IMR90 and BJ cells, respectively) induced by DNA damage (Kang et al 2015 ; Lee Y, Kim, Jeon, et al 2021 ; Lee Y, Kim, Kim, et al 2021 ). We found that woad extracts selectively sensitized senescent BJ cells over their normal counterpart, which is comparable to the previously identified navitoclax (Zhu et al 2016 ); however, woad extracts did not affect normal nor senescent IMR90 cells ( Figure 2 A and B), being consistent with results from our focused screen that utilized human dermal fibroblasts ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we decided to examine whether this is also the case for woad extracts. We employed two gold-standard models of senescent cell lines: senescent human lung and foreskin fibroblasts (IMR90 and BJ cells, respectively) induced by DNA damage (Kang et al 2015 ; Lee Y, Kim, Jeon, et al 2021 ; Lee Y, Kim, Kim, et al 2021 ). We found that woad extracts selectively sensitized senescent BJ cells over their normal counterpart, which is comparable to the previously identified navitoclax (Zhu et al 2016 ); however, woad extracts did not affect normal nor senescent IMR90 cells ( Figure 2 A and B), being consistent with results from our focused screen that utilized human dermal fibroblasts ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cells were maintained in 3% O 2 and cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with 15% fetal bovine serum (FBS), penicillin/streptomycin, and 0.1 mM nonessential amino acids. Senescence was induced by treatment with bleomycin (10 μg/ml for 24 h; Cayman Chemicals) or replicative exhaustion, as described previously (Kang et al 2015 ; Lee Y, Kim, Jeon, et al 2021 ; Lee Y, Kim, Kim, et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%